Building sustainable communities for sustainable development: An evidence‐based behavior change intervention to reduce plastic waste and destructive fishing in Southeast Asia. (5th February 2022) - Simmons, Erik Christopher; Sanders, Matthew
Abstract: Environmental crises often stem back to how humans make decisions and behave. Thus, the extent to which we can successfully address these challenges will depend on the extent to which we can design and deliver effective behavioral change interventions. This project examines how complex behavioral change interventions can be applied to modify human behavior of villagers living in coastal communities. Our work aimed to increase adoption of sustainable behaviors, protect marine biodiversity, improve community wellbeing, increase individual psychosocial skills and executive functions, and increase communal resiliency and adaptability. We conducted pilot and feasibility efficacy trials in two low‐resource coastal communities in Indonesia and Philippines. We used a single site case study and a quasi‐experimental design with control‐treatment matching to evaluate the intervention. Results include increased sustainable behaviors (e.g., recycling), increased prosocial behaviors (e.g., positive communication), and increased perceptions of empowerment for groups exposed to the intervention.